Assessing the contributions of non-bank financial institutions (NBFI) and ELS issuance to systemic risk in Korea - Jong Soo Hong (KDI Journal of Economic Policy, 2024)
Since the Global Financial Crisis of 2008-2009, the importance of non-bank financial institutions in macroprudential management has increased significantly. Consequently, major countries and international financial institutions have been actively discussing and implementing macroprudential supervision and regulation for non-bank financial institutions (NBFI). In this context, this paper analyzes the systemic risk of both banks and non-bank sectors (securities firms and insurance companies) in South Korea over different time periods. Using the widely recognized ΔCoVaR methodology for measuring systemic risk, the analysis reveals that systemic risk increased substantially across all three sectors (banks, securities firms, and insurance companies) during the Global Financial Crisis, the European Sovereign Debt Crisis, and the COVID-19 pandemic. Although the banking sector exhibited relatively high systemic risk compared to the securities and insurance sectors, the relative differences in systemic risk varied across the different crisis periods. Notably, during the margin call crisis in March of 2020, the gap in systemic risk between the banking and securities sectors decreased significantly compared to that during both the Global Financial Crisis and the European Sovereign Debt Crisis, indicating that securities firms had a more substantial impact on risk in the overall financial system during this period. Furthermore, I analyze the impact of the issuance of equity-linked securities (ELS) by financial institutions on systemic risk, as measured by ΔCoVaR, finding that an increase in the outstanding balance of ELS issuance by financial institutions had an impact on increasing ΔCoVaR during the three crisis periods. These findings underscore the growing importance of non-bank financial institutions in relation to South Korea's macroprudential management and supervision. To address this evolving landscape, enhanced monitoring and regulatory measures focusing on non-bank systemic risk are essential components of maintaining financial stability in the country.
Keywords: G01; G23; G28; G32; 330; NBFI; Systemic Risk; Macroprudential Policies; Financial Stability; Equity-linked Seurities